Assessment of Students Knowledge and Attitude toward Hepatitis B and C in Sohag University/Egypt - Ghona Abd El-Nasser; Eman Abed El-baset (Kufa Journal for Nursing Sciences)
Objective: To determine the effect of health education on the student knowledge in Sohag University regarding hepatitis B and C and to compare with four different faculties educational fields.